Task-oriented wireless communications with AI and IoT devices - Png, Justin Jun Leng (Nanyang Technological University, 2024)
The primary goal of this report is to showcase the development of the Final year project for Task-Oriented Wireless Communications with AI and IoT Devices. Understanding Task-Oriented Wireless Communications and methods for task extraction using AI with IoT devices is necessary for this project.